A novel high accuracy optical path difference compensation method based on phase difference technology. (February 2021) - Zheng, Hong-kun; Lv, Ri-qing; Zhao, Yong; Wang, Xi-xin; Lin, Zi-ting; Zhou, Yi-fan; Zhao, Qiang
Highlights: The proposed method realizes the large dynamic range and the high accuracy demodulation with less extra computation, which integrates the advantages of DGT and phase methods. By applying phase difference compensation technology, the OPD demodulation resolution achieves 45.37 pm, and the demodulation accuracy improves about 10, 000 times. The proposed method can also combine with other methods for improving the demodulation accuracy. Abstract: A novel method, which is based on the phase difference between the filtered spectrum and simulated spectrum, is proposed to compensate for the optical path difference (OPD) demodulation error of the interferometer sensors. With applying the phase difference technology, large dynamic range OPD demodulation with high accuracy is realized. Its principle is deduced by theoretical analysis. The numerical simulation is conducted in the presence of noise, amplitude variation, and constant offset, verifies that the proposed method is robust. The strain experiment result shows that the demodulation resolution is 45.37 pm at the cavity length of around 328 μm. The demodulation accuracy improves about 10, 000 times compares with the DGT method, and the demodulation resolution is achieved to the same order as the most advanced method with less computation. And the phase difference technology can be applied to other demodulation methods for high demodulation accuracy.